2022
DOI: 10.1111/jvh.13746
|View full text |Cite
|
Sign up to set email alerts
|

HCV hotline facilitates Hepatitis C elimination during the COVID‐19 pandemic

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…We read with great interest the manuscript published by Hartl et al 1 showing that efforts for hepatitis C virus (HCV) elimination can be made even during infectious disease outbreaks. Recently,…”
Section: Monkeypox Outbreak As An Opportunity To Identify New Cases O...mentioning
confidence: 99%
“…We read with great interest the manuscript published by Hartl et al 1 showing that efforts for hepatitis C virus (HCV) elimination can be made even during infectious disease outbreaks. Recently,…”
Section: Monkeypox Outbreak As An Opportunity To Identify New Cases O...mentioning
confidence: 99%
“…To our knowledge, this is the first evaluation of a program which referred patients directly to a remote online evaluation system (HCV e-consult DTT program) with subsequent successful HCV treatment initiation and completion by midlevel providers, highlighting a potential model for other integrated healthcare systems. There exist other telehealth programs that have been demonstrated to be effective for HCV treatment 12 15 . Of particular note, at the VA, one study found that sites that offered video conferencing between primary care providers and people living with HCV as part of the HCV VA-ECHO program had higher treatment initiation rates than sites that did not offer this 16 .…”
Section: Discussionmentioning
confidence: 99%
“…To remove information and treatment barriers, a physician-based hotline operated by specialists at the viral hepatitis clinic of the Medical University of Vienna offers a low-barrier tool for communication and linkage to care [ 15 , 19 ]. In 2019, 79 antiviral therapies with an SVR4 rate of 98.0% were initiated via this “HepC Phone” [ 15 ].…”
Section: Introductionmentioning
confidence: 99%